Identification of Neospora caninum in aborted bovine fetuses of Southern Chile - Moroni, Manuel (2018)
The aim of this study was to identify Neospora caninum in histologic sections of brain and optic nerve of aborted bovine fetuses. Sections of these tissues from 296 aborted bovine fetuses from Southern Chile, submitted between 2000 and 2010, to the Instituto de Patología Animal of the Universidad Austral de Chile were analyzed. Forty-four (14.9%) fetuses had microscopic lesions compatible with bovine neosporosis, including gliosis, necrosis, intralesional protozoan cysts and neuritis of optic nerves. N. caninum was identified by immunohistochemistry in brain sections of 27 cases (9.1%) with compatible lesions. Positive immunostaining was also found in the optic nerves of 13 cases (4.4%) with neuritis. N. caninum DNA was identified by PCR in brain sections in 31 cases (10.5%). In total, 36 cases (12.2%) were positive by either technique. Phylogenetic analysis of the ITS1 gene sequence of N. caninum revealed a high degree of conservation among different isolates. This is the first report of N. caninum-associated optic neuritis in cattle and also the first report of confirmed bovine abortion associated with this parasite in Chile.